Continuous detection of trace level concentration of oil droplets in water using microfluidic AC electroosmosis (ACEO)1. Issue 86 (18th September 2015) - Das, D.; Yan, Z.; Menon, N. V.; Kang, Y.; Chan, V.; Yang, C.
<x xml:space="preserve">Abstract</x> A novel design for high throughput detection of oil micro-droplets in water which is important to environmental oil spill monitoring agencies.